"Professional communicative competence of future engineers-pedagogues" - Markova, V. N. (Problems of Engineer-Pedagogical Education, 2018)
The article considers the aspects of professional communicative competence of future engineers-pedagogues and defines the essence of professional communicative competence of an engineer-educator. The nuances of the meaning of the concept "competence" are analyzed. Special emphasis is placed on the types of communicative activities of an engineer-pedagogue. The author regards professional competence of an educator as the unity of his/her theoretical and practical readiness to perform pedagogical activity. Professional communicative activity of an engineer-pedagogue consists in carrying out actions aimed at involving students in various activities, creating a team and organizing group activities. The activity of an engineer-pedagogue is directed at establishing pedagogically appropriate relations between the teacher and his/her students, their parents, other teachers, and representatives of the public. Specialists of any sphere of activity must have general competence indispensable for living in modern society and solving any situations, even those which are not related to specific professional activities. The article features peculiarities of professional communicative competence of future engineers-pedagogues.